First record of Herdmania pallida (Ascidiacea: Stolidobranchia: Pyuridae) in South Korea and genetic evidence suggesting cryptic diversity - Kwon, Soyeon; Lee, Jinho; Jeon, Sehun; Jeong, Hoon; Lee, Taekjun (Zootaxa, 2025)
The first record of Herdmania pallida (Ascidiacea: Stolidobranchia: Pyuridae) in South Korea is presented based on specimens collected from Jejudo Island. The specimens displayed morphological characteristics consistent with H. pallida, such as body form, branchial sac structure, and gonad arrangement, thus clearly differentiating them from other Herdmania species found in Korea (H. japonica, H. mirabilis, and H. momus). Seven partial sequences (856 bp) of the mitochondrial cytochrome c oxidase subunit I gene were obtained from the Korean specimens. Pairwise distance analysis indicated an average divergence of 9.8 % from three H. pallida reference sequences obtained from GenBank. The phylogenetic analysis further supported that the Korean specimens constitute a distinct clade and appear to be paraphyletic relative to the GenBank H. pallida sequences. These findings suggest potential cryptic diversity within the species and highlight the necessity for more extensive research. The study emphasizes the importance of broader geographic and population-level sampling, which will contribute significantly to better understanding species boundaries and clarifying the taxonomic status of H. pallida.